Prevalence and disparities in the first dental visit of preschool children aged 12-18 months in southern Brazil (Revista da Faculdade de Odontologia - UPF, 2018)
Objective: this study aimed to assess the use of dentalservices in a southern Brazilian city by children aged12-18 months and to verify the relationship betweensocioeconomic and demographic variables, as well asmaternal use of dental services, and presence of dentalcaries in the children. It also aimed to describe theprevalence of use of dental services by variables of disparity.Subjects and method: this cross-sectional studywas performed on the National Children’s VaccinationDay in 12 public health care centers in Pelotas, RS, Brazil.The data on demographic and socioeconomic status(children’s sex, number of children, family income, andmaternal education), pattern of maternal use of dentalservices, and children’s first dental visit were collectedusing a semi-structured interview answered by themothers. Clinical examination was performed to assessdental caries in the children. Chi-square and Fisher’sexact tests were performed to analyze the associationsand an equiplot graph investigated disparities in the prevalenceof the first dental visit of preschoolers. Results:most children had never been to the dentist (93.4%).The bivariate analysis showed that children who hadnever been to the dentist belonged to families with lowerincome, and their mothers presented low level ofeducation and did not use dental services. Conclusion:most children aged 12-18 months had never been to thedentist and there is a socioeconomic disparity in the useof dental services by preschool children.Keywords: Child. Dental services. Preventive dentistry.Preschool.